2020
DOI: 10.1007/s12369-020-00722-0
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Evaluations of a Therapy Dog and Biomimetic Robot: Influences of Animistic Beliefs and Social Interaction

Abstract: Social robots are being used increasingly across a range of settings, including in the context of therapeutic interactions with children. While research has shown that interaction with live therapy dogs can be calming and enjoyable for children, it is currently unclear whether social robots can produce similar outcomes. In this study, 11–12-year old children completed a questionnaire about their biophilic beliefs and attitudes to dogs and robots before engaging in two separate free-play, non-goal directed, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…The four remaining studies (Barber et al, 2020; Kahn et al, 2006; Loi et al, 2018; Moerman & Jansens, 2020) tested residential care facility staff ( N = 24) in Australia (Loi et al, 2018); typically developing children ( N = 80), aged from 2.83 to 6.17 years, in the United States (Kahn et al, 2006); students from a mainstream secondary school ( N = 34), with a mean age of 11.64 years, in the United Kingdom (Barber et al, 2020); and children on paediatric wards ( N = 9), aged between 4 and 13 years, in the Netherlands (Moerman & Jansens, 2020). See Table 1 for all study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The four remaining studies (Barber et al, 2020; Kahn et al, 2006; Loi et al, 2018; Moerman & Jansens, 2020) tested residential care facility staff ( N = 24) in Australia (Loi et al, 2018); typically developing children ( N = 80), aged from 2.83 to 6.17 years, in the United States (Kahn et al, 2006); students from a mainstream secondary school ( N = 34), with a mean age of 11.64 years, in the United Kingdom (Barber et al, 2020); and children on paediatric wards ( N = 9), aged between 4 and 13 years, in the Netherlands (Moerman & Jansens, 2020). See Table 1 for all study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…NeCoRO, a robotic cat (N = 1), possesses artificial intelligence aside from common mechanical components, allowing for a range of responses such as vocalizations of purring or meowing as well as non-verbal behaviours such as tail wagging and head turning (Libin & Cohen-Mansfield, 2004;Shibata et al, 1999). MiRo-E, a mammal-like biomimetic robot that looks like a long-eared dog (N = 1), has tactile, auditory and visual sensors and moves freely, indicating 'mood' by wagging its tail, producing noises, and changing the light colour on its body panels (Barber et al, 2020). Keepon, a yellow robotic toy in the shape of a snowman (N = 1), possesses small gimbals that allow its body to be manipulated and can be controlled by an operator or automatically (Kozima et al, 2009).…”
Section: Robots Used In Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomimetic Robotic Dogs, while not a topic within this review, have been discussed in a number of recent publications. Barber et al found that robotic dogs may be just as effective and a suitable replacement in certain situations with therapeutic benefits for children and young people [39]. The children spent a comparable amount of time stroking both the real-life dog and the robot and spent more time interacting with the robot, even though the children reported they significantly preferred the sessions with the living dog.…”
Section: Relationshipmentioning
confidence: 99%
“…A small creature-like robot, Keepon, was developed for both human-robot interaction and robot-therapy purposes by non-verbal interaction [29]. Another research work compared the therapeutic effects of a therapy dog and a robot dog and concluded that a robot device might support children [30]. However, these studies focused less on conversational interaction and dialogue management systems.…”
Section: B Mental Health Support By Agents/robotsmentioning
confidence: 99%